Para além do corpo, um lugar para a alma: reflexões sobre a noção de alma em Freud - Gueldini, Bruno (2023)
This work’s bet is based on the following consideration: it is necessary to talk about what seems to be nowhere and yet is there for someone, hence all the confusion. There’s the soul, as if hovering in the air. It cannot be conceptualized but remains permeated with particularities in the sense of its representation. In short, this was the starting point of this work, which aimed to investigate how an in-depth study of Freud's notion of soul can contribute to thinking about clinical reasoning. To this end, the text has been organized into three parts. The first follows a path that seeks to find some fundamental points for the understanding of Freud’s soul notion in epistemological discussions. We did it this way so that it was possible for the reader to understand, in the second part, that there is an ambiguity in the use of soul’s notion that functions as a kind of epistemological rupture paradigm proper to psychoanalysis, or, in other words, that the idea of soul may have been an essential operator for the construction of unconscious concept. From this development, the research emphasizes the presence of a rationality that precedes, transforms, and confers the status of the notion of soul in Freud's work. In the third part the reader will find more clearly that, although the notion of soul indicates a necessary condition for analytic listening, this condition is not sufficient to guarantee it. More than that, that there is nothing that can guarantee psychoanalytic listening, because, on the contrary, what the soul’s notion always situates is the irreducibility of the unconscious to the scientific pretensions of prediction and control. One of the main effects of this reading is the sliding of an imaginary scenario about the soul to a question about the soul logic of each one, which cannot be accomplished through a work of elucidation